Political engagement of Rehobot Christian High School's first-time voters in the 2024 presidential election - Karliani, Eli; Ikbal, Asep; Sangalang, Ronald Hadibowo; Tardimanto, Yuyuk; Indrawati, Lala; Cionita, Tezara (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This study aims to analyze how the political engagement of novice voters in the 2024 Presidential Election at Rehobot Christian High School Palangka Raya.  The largest data on voters in the 2024 Presidential Election is Generation Z, which is around 74.93%. This study uses a simple survey method on Rehobot Christian High School Palangka Raya students. The location was chosen because Rehobot Christian High School is a new school, and most of its students live in boarding schools but rarely receive political socialisation from the government or other institutions. The questionnaire consists of three aspects, namely knowledge, attitudes and political behaviour in the 2024 presidential election. The study results show that the average knowledge aspect falls into the medium category with a percentage of 46%, which indicates a potential for improvement in students' political knowledge in the 2024 presidential election. Regarding the average attitude of students regarding Political Engagement, which is included in the medium category with a percentage of 62%, there is also room for improvement in cultivating and strengthening attitudes regarding the responsibility to be involved in the presidential election. Meanwhile, from the behavioural aspect, the average student behaviour is in a very low category with a percentage of 43%, indicating a need for improvement in how novice voters actively participate in organisations or communities engaged in election volunteers.